PUSAT PELATIHAN AUTODEKS DENGAN PENDEKATAN HEMAT ENERGI DI MAKASSAR - Nawir, Muhammad Yahya; Rahayu, Irma; Mutmainnah, Mutmainnah (Nature: National Academic Journal of Architecture, 2014)
Autodeks as 2D and 3D software degsigners, for the construction industry, manufacturing, entertainment and education have formed the ATC (Autorizhed Training Centre) or training centers in each coutry. In Indonesia, the training center only be found in Java and Surabaya, but in the city of Makassar is not availablerepersentative. Makassar as the growing cities in Indonesia ideal be supported by ATC facility what a strategic, so that consumers in the city Makassar easier to obtain trsining and certification information. The designof commercial buildings such as ATC is necessary in large quantities, besides that, a great level of energy consumption for the building turned out to have devastating effect on the environment, therefore the design is focused on generating building Autodeks training center in Makassar are energy efficient.